2015
DOI: 10.1021/acschembio.5b00565
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Plk1 PBD Inhibitors Based on Poloxin Induce Mitotic Arrest and Apoptosis in Tumor Cells

Abstract: Polo-like kinase 1 (Plk1) is a central regulator of mitosis and has been validated as a target for antitumor therapy. The polo-box domain (PBD) of Plk1 regulates its kinase activity and mediates the subcellular localization of Plk1 and its interactions with a subset of its substrates. Functional inhibition of the Plk1 PBD by low-molecular weight inhibitors has been shown to represent a viable strategy by which to inhibit the enzyme, while avoiding selectivity issues caused by the conserved nature of the ATP bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 30 publications
(68 reference statements)
1
61
0
Order By: Relevance
“…Poloxin and thymoquinone can block the correct orientation of PLK1 , thereby preventing the mitosis of cancer cells [126]. A recent study showed that Poloxin-2, an optimized analogue of poloxin, has significantly improved potency and selectivity over poloxin in inducing mitotic arrest and apoptosis in cultured human cancer cells [128].…”
Section: Plk1 and Human Cancermentioning
confidence: 99%
“…Poloxin and thymoquinone can block the correct orientation of PLK1 , thereby preventing the mitosis of cancer cells [126]. A recent study showed that Poloxin-2, an optimized analogue of poloxin, has significantly improved potency and selectivity over poloxin in inducing mitotic arrest and apoptosis in cultured human cancer cells [128].…”
Section: Plk1 and Human Cancermentioning
confidence: 99%
“…In an effort to further improve the efficacy of Poloxin, recently, Scharow and colleagues reported identification of the optimized analog Poloxin-2, which was shown to have significantly improved potency and selectivity over Poloxin (72). Poloxin-2 arrests mitosis in human tumor cell lines and induces apoptosis at lower micromolar concentrations (IC50=1.36 umol/L), as compared with the IC50 of 4.8 umol/L of its predecessor (70).…”
Section: Plk1 As a Drug Targetmentioning
confidence: 99%
“…Moreover, we showed that TQ and Poloxin, compounds that provided the first proof of concept for PBD inhibition by non-peptide small molecules are also alkylators of nucleophilic amino acid side chains. The potential of Poloxin to act as an alkylator on the PBD was proposed based on SAR in a recent study, but protein alkylation by Poloxin was not demonstrated52.…”
Section: Discussionmentioning
confidence: 99%